Climbing the Activity Volcano: Core–Shell Ru@Pt Electrocatalysts for Oxygen Reduction. Issue 1 (26th November 2013) - Jackson, Ariel; Viswanathan, Venkatasubramanian; Forman, Arnold J.; Larsen, Ask H.; Nørskov, Jens K.; Jaramillo, Thomas F.
Abstract We outline a systematic approach to develop active catalyst materials for an electrochemical reaction. The strategy allows one to tune binding energies of oxygen reaction intermediates on a catalyst surface by taking advantage of two effects: weakening oxygen binding energies by means of thin‐film overlayers, and strengthening oxygen binding energies through nanoscale effects. By engineering a core–shell nanoparticle morphology with the appropriate dimensions, that is, the thickness of the overlayer and the size of the nanoparticle, bonding properties can be modified to improve the catalytic activity of the core–shell system. We demonstrate the application of this strategy for oxygen reduction by identifying Ru@Pt as a candidate material using density functional theory calculations, and then use these calculations to guide the synthesis of active Ru@Pt core–shell catalysts. The Ru@Pt particles, synthesized using a wet chemical method, exhibit ∼2 times higher specific activity (based on electrochemical active surface area) than state‐of‐the‐art Pt/C from TKK.